“From out the Portals of My Brain”: William Blake’s Partus Mentis and Imaginative Regeneration - Annalisa Volpone (Humanities, 2024)
Partus mentis (the parturition of the mind) brings together the following two significant aspects of Romantic culture and ideology: the exploration into human generation, and the process of how imagination forms an idea and makes the mind creatively productive. This article suggests that analyzing William Blake’s portrayal of imagination through the partus mentis trope can enhance our comprehension of how he illustrates and employs this faculty in his works. In Blake’s partus mentis, the analogy between the brain and the womb is pivotal. The brain is seen as a host for ideas that are conceived through imagination, and once they are brought to life, they become art. This is a vital component of Blake’s cosmogony, tying into his personal reinterpretation of biblical Genesis and his concept of the Human Form Divine. It also includes his response to medical theories and practises regarding generation and life. This article pays close attention to the medico-cultural discourse that was contemporary to Blake, and its wide use of the ‘analogy’, which defined the episteme of the long eighteenth century. The analogy approach was later challenged by the ‘epistemology of the visual’, which emphasized the use of anatomical atlases, wax models, and dissections for direct experiential insights into bodily functions and processes, particularly of the brain and the womb. This article argues that Blake is able to transcend these two epistemologies while harnessing specific elements from each.